Protected Culture for Vegetable and Small Fruit Crops: Types of Structures - Shinsuke Agehara; Gary Edward Vallad; Emmanuel A. Torres-Quezada (EDIS)
A protective structure is defined as any structure designed to modify the environment in which plants are grown. Protective structures, such as greenhouses, screen houses, and tunnels, are known worldwide as production systems for high-quality vegetable and fruit crops.